Microplasma-enabled colloidal nitrogen-doped graphene quantum dots for broad-range fluorescent pH sensors. (15th October 2020) - Kurniawan, Darwin; Chiang, Wei-Hung
Abstract: Here we report a liquid-phase, bottom-up synthesis of photoluminescent colloidal nitrogen-doped graphene quantum dots (NGQDs) under ambient conditions using atmospheric-pressure microplasmas. The nucleation, growth, and simultaneously N doping of GQDs were achieved using a single plasma-liquid process. The as-synthesized NGQDs showed a 6.39 nm averaged diameter with a narrow size distribution and room-temperature excitation-dependent photoluminescence with a quantum efficiency up to 30%. The stable colloidal NGQDs with polar nitrogen-doping configurations and oxygen-containing functional groups on surfaces exhibited protonation/deprotonation properties under the pH value ranging from 1.25 to 13.56 and can be used for broad-range pH detection. Our study not only provides a simple, scalable, and environmental-friendly method to synthesize NGQD under ambient condition but also the fundamental understanding of pH detection using NGQDs. Graphical abstract: Image 1